Kandahar the intriguing untold story - Makhmalbaf, Mohsen; Makhmalbaf Film House (Iran : Makhmalbaf Film House, 2002)
Filmed on the Iran/Afghanistan border using a semi-documentary style, Kandahar chronicles the perilous journey undertaken by an expatriate female journalist, Nafas, to reach the city of Kandahar, where she hopes to rescue her sister from committing suicide. Her journey is told through a series of vignettes, each one of which lifts the veil on the abrogation of freedom for women under the Taliban, the general poverty and hardship experienced by all Afghans, and the indoctrination of young boys into violence and religion
Production manager, Abbas Saghrisaz ; editor, Mohsen Makhmalbaf
VCD format
Keywords: Women in motion pictures; Arabs in motion pictures; Afghanistan -- Social conditions -- Drama